Soil Carbon Storage Controlled by Interactions Between Geochemistry and Climate - Casanova-Katny, A (Nature Publishing Group, 2015)
Soils are an important site of carbon storage. Climate is generally regarded as one of the primary controls over soil organic carbon, but there is still uncertainty about the direction and magnitude of carbon responses to climate change. Here we show that geochemistry, too, is an important controlling factor for soil carbon storage. We measured a range of soil and climate variables at 24 sites along a 4,000-km-long north-south transect of natural grassland and shrubland in Chile and the Antarctic Peninsula, which spans a broad range of climatic and geochemical conditions. We find that soils with high carbon content are characterized by substantial adsorption of carbon compounds onto mineral soil and low rates of respiration per unit of soil carbon; and vice versa for soils with low carbon content. Precipitation and temperature were only secondary predictors for carbon storage, respiration, residence time and stabilization mechanisms. Correlations between climatic variables and carbon variables decreased significantly after removing relationships with geochemical predictors. We conclude that the interactions of climatic and geochemical factors control soil organic carbon storage and turnover, and must be considered for robust prediction of current and future soil carbon storage. © 2015 Macmillan Publishers Limited. All rights reserved.